Autism spectrum disorder and co-occurring developmental, psychiatric, and medical conditions among children in multiple populations of the United States - Levy, Susan E; Giarelli, Ellen; Lee, Li-Ching; Schieve, Laura A; Kirby, Russell S; Cunniff, Christopher; Nicholas, Joyce; Reaven, Judy; Rice, Catherine E (Journal of developmental and behavioral pediatrics, 2010)
Autism spectrum disorders (ASDs) often co-occur with other developmental, psychiatric, neurologic, or medical diagnoses. This study examined co-occurring non-ASD diagnoses and symptoms in a population-based cohort of 8 year olds identified with ASD. Data on 2,568 children meeting surveillance case definition for ASD were collected by a multi-site surveillance program. Information was systematically abstracted and reviewed from existing health and education source records and systematically entered into a summary record in a secure database. Eighty-one percent of study children were male; 63% white, 23% black, 14% Hispanic, Asian, or not stated. When age of ASD classification was available, 20% were classified before age 3 years, 36% between ages 3 and 5 years, and 44% after age 5 years. The co-occurrence of > or = 1 non-ASD developmental diagnoses was 83%, > or = 1 psychiatric diagnoses was 10%, > or = 1 neurologic diagnoses was 16%, and at least one possibly causative genetic or neurologic diagnosis was 4%. Children with a previous ASD classification and co-occurring psychiatric or neurologic conditions were more likely to be diagnosed or classified at a later age. Each category of co-occurring non-ASD diagnosis was significantly increased in children whose records did not include an ASD diagnosis or educational classification but who met surveillance criteria for ASD. These data highlight the need for clinicians to keep in mind the high prevalence of associated diagnoses with an ASD diagnosis, and the possibility that in younger children other symptoms or disorders may be masking or obscuring core symptoms of ASD, which would lead to a diagnosis.